The relationship between pelvic floor muscle's strength and severity of urinary incontinence with quality of life in women with stress urinary incontinence - Gholamhosein Nassaj; Parvin Amirpour; Shadab Shahali; Zahra Sarikhani (Mashhad University of Medical Sciences, 2017)
Introduction: Stress urinary incontinence is a common problem among women, which negatively affects all aspects of a woman's life. This study was performed with aim to investigate the relationship between pelvic floor muscles' strength and severity of urinary incontinence with quality of life in women with stress urinary incontinence. Methods: This cross-sectional study was performed on 126 women with stress urinary incontinence in Ahvaz in 2015-2016. To determine the type of incontinence and its severity, the questionnaires of urinary incontinence (QUID) and urinary incontinence severity index were used. Pelvic floor muscle's strength was evaluated manually. The quality of life was measured using a questionnaire of measuring quality of life in women with urinary incontinence (IQOL). Data were analyzed using SPSS statistical software (version 22) and Chi-square test. P Results: In this study, there is a significant relationship between the severity of urinary incontinence and muscles' strength with quality of life (p <0.0001). It means that women with severe urinary incontinence and lower pelvic floor muscles' strength had lower quality of life. Conclusion: Women with more severe form of urinary incontinence and weaker pelvic floor muscles have lower quality of life, thus it is essential to consider the strategies to strengthen pelvic floor muscles and improve urinary tract health.